Energy efficiency in production of swiftlet edible birds nest - Alpandi, Rabiatul Munirah; Kamarudin, Fakarudin; Wanke, Peter; Muhammad Salam, Muhammad Syafiq; Hussain, Hafezali Iqbal (Multidisciplinary Digital Publishing Institute, 2022)
The swiftlet edible bird’s nest (EBN) is a ranching industry in which the ranchers do not have to own the birds and are not required to prepare the food as the birds will find their own. However, the ranchers need to provide the ranches and attract the birds for nesting. This study examined a two-stage analysis on energy efficiency and greenhouse gas (GHG) emission in the swiftlet EBN production in Johor Bahru, Johor, Malaysia. In the first stage, non-parametric data envelopment analysis (DEA) was used to measure the efficiency score. The results revealed that out of 150 ranches, 7.33% and 40.67% of the ranches were efficient under the Charnes, Cooper, and Rhodes (CCR) and Banker, Charnes, and Cooper (BCC) models, respectively. The average of technical, pure technical, and scale efficiencies are 0.35361, 0.93071, and 0.37199, respectively. Analysis on optimum energy requirement and energy savings showed the total energy input that could be saved by the inefficient ranches was 0.89391 MJ/sqft−1 (63.87%). In addition, the inefficient ranches could reduce emissions by 63.86% (0.04497 kg Co2eq/sqft−1). In the second stage of analysis using the Tobit model, the results reported that a nesting plank was the factor with the most significantly positive effect on the ranch efficiency to improve their efficiency in energy consumption savings and emissions reduction in the EBN production.